2017
DOI: 10.1111/add.13913
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of self‐reported smoking abstinence in clinical trials of hospital‐initiated smoking interventions

Abstract: Aims To estimate the prevalence and predictors of failure biochemically to verify self-reported abstinence among participants enrolled in trials of hospital-initiated smoking cessation interventions. Design Comparison of characteristics between participants who verified and those who failed to verify self-reported abstinence. Settings Multi-site randomized clinical trials conducted between 2010 and 2014 in hospitals across the United States. Participants Recently hospitalized smokers who reported tobacco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…Times Salivary Cotinine (mml/dl) FTND CPD Coefficient (95% CI) P value Coefficient (95% CI) P value Coefficient (95% CI) P value A 2 vs 1 À95.5 (À116.2 to À74.8) <0.001 À4.4 (À5.1 to À3.7) <0.001 À10.7 (À13.1 to À8.3) <0.001 3 vs 1 À71.8 (À92.5 to À51.1) <0.001 À3.2 (À3.9 to À2.5) <0.001 À11.3 (À13.7 to À8.9) <0.001 3 vs 2 23.7 (3.1-44.4) 0.024 1.3 (0.6-2.0) <0.001 À0.6 (À3.0 to 1.8) 0.640 B 2 vs 1 À57.6 (À78.2 to À36.9) <0.001 À2.7 (À3.4 to À2.0) <0.001 À9.0 (À11.4 to À6.6) <0.001 3 vs 1 À46.0 (À66.7 to À25.3) <0.001 À2.5 (À3.2 to À1.8) <0.001 À5.9 (À8.3 to À3.5) <0.001 3 vs 2 11.6 (À9.1 to 32.2) 0.274 0.2 (À0.5 to 0.9) 0.522 3.1 (0.7-5.5) 0.010 C 2 vs 1 À3.9 (À25.2 to 17.4) 0.720 0.0 (À0.7 to 0.7) 1.000 À0.9 (À3.4 to 1.6) 0.470 3 vs 1 À5.9 (À27.2 to 15.4) 0.588 0.2 (À0.5 to 0.9) 0.621 À0.5 (À3.0 to 2.0) 0.683 3 vs 2 À2.0 (À23.3 to 19.3) 0.854 0.2 (À0.5 to 0.9) 0.621 0.4 (À2.0 to 2.9) 0.754 D 2 vs 1 À86.8 (À107.4 to À66.1) <0.001 À3.2 (À3.9 to À2.5) <0.001 À10.6 (À13.0 to À8.2) <0.001 3 vs 1 À71.9 (À92.6 to À51.2) <0.001 À3.5 (À4.2 to À2.8) <0.001 À10.1 (À12.5 to À7.7) <0.001 was a quantitative and more reliable method compared to most previous studies which using self-reported measurements [33]. Previous studies have shown that five F3 anodal stimulations reduce CPD by about 30% compared to the sham group [16].…”
Section: Groupsmentioning
confidence: 63%
See 1 more Smart Citation
“…Times Salivary Cotinine (mml/dl) FTND CPD Coefficient (95% CI) P value Coefficient (95% CI) P value Coefficient (95% CI) P value A 2 vs 1 À95.5 (À116.2 to À74.8) <0.001 À4.4 (À5.1 to À3.7) <0.001 À10.7 (À13.1 to À8.3) <0.001 3 vs 1 À71.8 (À92.5 to À51.1) <0.001 À3.2 (À3.9 to À2.5) <0.001 À11.3 (À13.7 to À8.9) <0.001 3 vs 2 23.7 (3.1-44.4) 0.024 1.3 (0.6-2.0) <0.001 À0.6 (À3.0 to 1.8) 0.640 B 2 vs 1 À57.6 (À78.2 to À36.9) <0.001 À2.7 (À3.4 to À2.0) <0.001 À9.0 (À11.4 to À6.6) <0.001 3 vs 1 À46.0 (À66.7 to À25.3) <0.001 À2.5 (À3.2 to À1.8) <0.001 À5.9 (À8.3 to À3.5) <0.001 3 vs 2 11.6 (À9.1 to 32.2) 0.274 0.2 (À0.5 to 0.9) 0.522 3.1 (0.7-5.5) 0.010 C 2 vs 1 À3.9 (À25.2 to 17.4) 0.720 0.0 (À0.7 to 0.7) 1.000 À0.9 (À3.4 to 1.6) 0.470 3 vs 1 À5.9 (À27.2 to 15.4) 0.588 0.2 (À0.5 to 0.9) 0.621 À0.5 (À3.0 to 2.0) 0.683 3 vs 2 À2.0 (À23.3 to 19.3) 0.854 0.2 (À0.5 to 0.9) 0.621 0.4 (À2.0 to 2.9) 0.754 D 2 vs 1 À86.8 (À107.4 to À66.1) <0.001 À3.2 (À3.9 to À2.5) <0.001 À10.6 (À13.0 to À8.2) <0.001 3 vs 1 À71.9 (À92.6 to À51.2) <0.001 À3.5 (À4.2 to À2.8) <0.001 À10.1 (À12.5 to À7.7) <0.001 was a quantitative and more reliable method compared to most previous studies which using self-reported measurements [33]. Previous studies have shown that five F3 anodal stimulations reduce CPD by about 30% compared to the sham group [16].…”
Section: Groupsmentioning
confidence: 63%
“…Similarly, in a study on 600 adult smokers, treated with slow-release 300 mg bupropion and counseling, the quit rate at 26 weeks was 21.0% vs. 13.7% in placebo group [32]. However, What should be considered in comparison of these studies is that counseling was not provided in the current study, and the smoking abstinence measurement scale was a quantitative and more reliable method compared to most previous studies which using self-reported measurements [33]. Previous studies have shown that five F3 anodal stimulations reduce CPD by about 30% compared to the sham group [16].…”
Section: Discussionmentioning
confidence: 92%
“…Also, the intervention was conducted with smokers who had accepted a referral to treatment, which may have influenced the observed session attendance rates. Finally, cessation outcomes relied on self-report, suggesting these be interpreted with caution as mixed support exists for the veracity of self-reported smoking cessation (Scheuermann et al, 2017;SRNT, 2002;Velicer & Prochaska, 2004). While use of medications relied on self-report we were able to corroborate medication orders (i.e., whether participants were provided with medications) through medical chart review.…”
Section: Discussionmentioning
confidence: 86%
“…Accuracy of self-reported tobacco use after hospitalization has been measured elsewhere and accuracy of self-reported SLT use has been measured in India, and these studies suggest underreporting of continued tobacco is likely. 27,28 The prevalence of self-reported current tobacco use among hospitalized patients in Mumbai is lower than in the general Indian population. 29 In this sample, more hospitalized patients reported being former tobacco users than current tobacco users.…”
Section: Limitationsmentioning
confidence: 99%